2011
DOI: 10.1002/cbdv.201000264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Potential of Two Flavonoids Isolated from Limnophila Plants

Abstract: The antimicrobial potential of two bioflavonoids, i.e., 5,7-dihydroxy-4',6,8-trimethoxyflavone (1) and 5,6-dihydroxy-4',7,8-trimethoxyflavone (2), isolated from Limnophila heterophylla Benth. and L. indica (Linn.) Druce (Scrophulariaceae), respectively, were evaluated against the microbial strains Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, Alternaria solani, and Candida albicans. Compounds 1 and 2 exhibited moderate but broad antimicrobial activities against both Gram-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…aureus , whereas 5,6‐dihydroxy‐4,7,8‐trimethoxyflavone ( 14 ) was found to effectively kill B . subtilis by cell lysis (Brahmachari et al, ). When screening natural products for inhibition of β‐ketoacyl acyl carrier protein synthase (Chitsazian‐Yazdi et al, ), Lee et al () found that the 3,6‐dihydroxyflavone ( 50 ) was very effective.…”
Section: Mechanism Of Antibacterial Activitymentioning
confidence: 99%
“…aureus , whereas 5,6‐dihydroxy‐4,7,8‐trimethoxyflavone ( 14 ) was found to effectively kill B . subtilis by cell lysis (Brahmachari et al, ). When screening natural products for inhibition of β‐ketoacyl acyl carrier protein synthase (Chitsazian‐Yazdi et al, ), Lee et al () found that the 3,6‐dihydroxyflavone ( 50 ) was very effective.…”
Section: Mechanism Of Antibacterial Activitymentioning
confidence: 99%
“…Also 5,7-dihydro-3,4′,6-tri-methoxyflavone, isolated from the Dodonaea angustifolia gave promising growth inhibitory effects against Saccharomyces cerevisiae with the MIC value of 3.9 µg/ml [95]. Moreover, 5,6-dihydroxy-3',4',7-trimethoxyflavone was found to affect the fungal development through disruption of the fungal metabolic pathway and of the fungal cell function [96]. Subsequently, we suggest that 5,6-dihydroxy-3,4,7-trimethoxy flavone (12) in T. brownii stem wood, might have a similar mechanism of action to inhibit fungal growth.…”
Section: Discussionmentioning
confidence: 99%
“…MIC of the compound for E. coli and A. solani were found to be 200 and 250 µg/ml, respectively. [53] Other Activities Brahmachari et al [54] evaluated nevadensin for its cyclooxygenase-1 and 2 (COX-1 and COX-2) inhibitory efficacy by employing the COX catalysed prostaglandin biosynthesis assay in vitro method. The compound was found to exhibit moderate inhibitory activity against COX-1 and weak activity against the COX-2 with respective percent inhibition of 7.37 and 0.65% both at a dose of 10 µM.In addition, pharmacological experiments have shown that the flavonoid possesses expectorant and antitussive actions.…”
Section: Anti-tumour and Anti-cancer Activitymentioning
confidence: 99%